IMPLEMENTASI PENGUATAN PROFIL PELAJAR PANCASILA: MENUMBUHKAN SIKAP MANDIRI SISWA MELALUI KEGIATAN MARKET DAY DI SEKOLAH DASAR - Hidayat, Wahyu; Zarkasih Putro, Khamim; Rahmatsyah (As-Sulthan Journal of Education, 2025)
This research aims to explore and analyze the effectiveness of Market Day activities in strengthening student profiles related to Pancasila values in elementary schools. The research method used is qualitative with a case study approach. Data collection was carried out through observation, interviews and document analysis. Research findings show that Market Day can effectively introduce, internalize and apply Pancasila values to students. Apart from that, this activity also facilitates the development of social skills, entrepreneurship, and the courage to innovate. The implications of this research provide an important contribution to character education at the elementary level and guide other schools that wish to implement similar strategies in increasing understanding and appreciation of Pancasila values among students.